Factors Affecting Attitudes towards Cohabitation among Iranian Youth - Reyhane Ghasemi Neyasar; Rasoul Sadeghi; Fatemeh Torabi (جامعه شناسی کاربردی, 2025)
Introduction In previous decades, marriage has been more prevalent, while cohabitation has been largely limited to specific social groups. However, attitudes toward cohabitation are shifting in many countries, resulting in its increased acceptance and prevalence. In Iran, although some young people still hold disapproving views about cohabitation, its occurrence is rising, particularly in major cities like Tehran. The theory of the second demographic transition highlights that growing individualism, secularism, and gender egalitarianism have contributed to the emergence of new family structures, including cohabitation. This article aimed to explore young individuals' perspectives on cohabitation and analyze the factors influencing these attitudes.